Harnessing the Power of Social Media, Pricing Strategies, Brand Image, and Product Quality in Purchase Decisions - Fitriana, Annisha; Komala, Lenda (SAN Scientific, 2024)
The purpose of this study is to ascertain whether ASUS brand purchasing decisions are influenced by social media, pricing, brand perception, and product quality laptops. The population of this research is YARSI University students who buy or use ASUS brand laptops. The sampling technique uses a non-probability method, using a purposive sample approach by sending out surveys. Multiple regression analysis, the partial t-test, and the simultaneous f-test are the data analysis techniques that are employed. The study's findings indicate that (1) social media influence has a negligible and unfavorable impact on consumers' decisions to buy. Price has a negligible and unfavorable influence on decisions made about purchases. (3) Buying decisions are positively and significantly impacted by brand image. (4) Buying decisions are positively and significantly impacted by product quality. (5) Every independent variable simultaneously has a big impact on buying decisions. The research's managerial implications show that businesses must focus on integrated marketing strategies on social media to increase interaction and engagement with consumers. Competitive and transparent price management can increase product attractiveness, while a positive brand image needs to be built through consistent and innovative communication.